2019
DOI: 10.20944/preprints201905.0103.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of in ovo Injection of L-Arginine in Different Chicken Embryonic Development Stages on Post-hatch Growth Performance, Immune Response and Muscle Development Proteins

Abstract: The objective of this study was to evaluate the effect of in ovo injection of L-arginine (L-Arg) into Ross broiler eggs at different embryonic developmental stages on their survival, hatchability, and body weight (BW). Additionally, we have analyzed the levels of serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic-pyruvic transaminase (SGPT), protein expression of heat shock proteins (HSPs), also we have the determined micronuclei (MN) and nuclear abnormality (NA). Results showed that survival an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Also the improvement of hatchability by 6.54 % compared with control group was reported by Kalantar et al (2019) who injected broiler chickens eggs with Coenzyme Q10 before incubation. Similarly, in ovo administration of L-Arginine at the rate of (100 µg/µl/egg) on the 14 th day of incubation resulted in improvement of survival and hatching rates (Subramaniyan et al 2019). Regarding the hatched chick weight, the result showed that chicks' weight at hatch was significantly higher (p≤0.001) in resveratrol injected eggs compared to sham or intact control groups.…”
Section: Results and Discussion Hatching Traitsmentioning
confidence: 93%
“…Also the improvement of hatchability by 6.54 % compared with control group was reported by Kalantar et al (2019) who injected broiler chickens eggs with Coenzyme Q10 before incubation. Similarly, in ovo administration of L-Arginine at the rate of (100 µg/µl/egg) on the 14 th day of incubation resulted in improvement of survival and hatching rates (Subramaniyan et al 2019). Regarding the hatched chick weight, the result showed that chicks' weight at hatch was significantly higher (p≤0.001) in resveratrol injected eggs compared to sham or intact control groups.…”
Section: Results and Discussion Hatching Traitsmentioning
confidence: 93%